Minimasi Defect pada Proses Loading-Unloading Galon Menggunakan Pendekatan Lean Manufacturing dan Value Stream Mapping - yuniawati, Ratna Diah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Logistics processes, particularly in the loading and unloading area, pose a critical challenge for the Bottled Drinking Water (AMDK) industry, as they have the potential to reduce profitability due to waste. This study aims to eliminate non-productive activities in the distribution line of PT XYZ using a Lean Manufacturing approach. By integrating Value Stream Mapping (VSM) to map process flows and the Waste Assessment Model (WAM) to weight operational issues, this study examines the company’s operational problems. The identification results indicate that defect is the most dominant form of waste, contributing 24.37% of the total waste variability, which significantly hampers distribution flow. Root Cause Analysis (RCA) highlights employee discipline and operational work instructions as the primary factors causing these defects. As a mitigation strategy, this study formulates improvement recommendations based on restructuring work instructions and strengthening employee discipline standards to reduce defect rates and accelerate service lead time.